Media Fun Thinkers Pada Materi Perubahan Energi Untuk Siswa Sekolah Dasar - I Komang Wahya Sudhyatmika; I Gusti Ayu Tri Agustiana; Gede Nugraha Sudarsana (Mimbar Ilmu, 2022)
Lack of interest in student learning can affect student learning outcomes, so it is necessary to develop media that can increase student interest in learning. The purpose of this study was to analyze the validity of the Fun thinker's media with a literature review on the energy change material for grade IV elementary school. This type of research is developed using the ADDIE research model. The subjects of this research are 2 material experts, 2 media experts. The test subjects were 1 teacher and 10 students. The data collection method used is a non-test instrument. The data collection instrument used is a questionnaire. The data obtained were analyzed using descriptive quantitative statistical data analysis techniques. The results of the analysis of media validity. Fun thinkers from material experts were in the range of 0.75-1.00, and media experts were in the range of 0.75-1.00, the percentage of practitioner response test results obtained a value of 99%, and the percentage of student response test results obtained a score of 97%. Media Fun thinkers are equipped with a literature review for fourth-grade elementary school students on energy change materials with high validity qualifications. It is concluded that Media Fun thinkers equipped with a literature review are suitable for the learning process.